2019
DOI: 10.1556/004.2019.010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in novel gastrointestinal and renal injury markers in the blood plasma of sheep following increasing intravenous doses of tolfenamic acid

Abstract: The administration of high doses of non-steroidal anti-inflammatory drugs (NSAID), such as tolfenamic acid (TA), has undesirable effects on different organs. Some novel biomarkers have been reported that can determine the gastrointestinal and renal injury caused by a high dose of NSAIDs or other toxic substances. This study was aimed at determining the changes in gastrointestinal (TFF2 and HYP), renal (NGAL and KIM-1) and cardiac (cTn-I, CK-MB) injury markers after the use of increasing intravenous doses of TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…In this study, the effect of TA on tissues and organs was not evaluated. TA had no effect on the gastrointestinal, renal, and cardiac markers when administered at single doses of 2 and 4 mg/kg in sheep, and no changes were observed in hematological, biochemical, and histopathological parameters following IV administration of 4 mg/kg every 24 hr for 14 days in rats (Patel et al., 2011; Yildiz et al., 2019). It has been reported that TA can cause side effects in cattle (18–20 mg/kg, CVMP, 1997), sheep (16 mg/kg, Corum et al., 2018), and horse (>4 mg/kg, Jaussaud et al., 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the effect of TA on tissues and organs was not evaluated. TA had no effect on the gastrointestinal, renal, and cardiac markers when administered at single doses of 2 and 4 mg/kg in sheep, and no changes were observed in hematological, biochemical, and histopathological parameters following IV administration of 4 mg/kg every 24 hr for 14 days in rats (Patel et al., 2011; Yildiz et al., 2019). It has been reported that TA can cause side effects in cattle (18–20 mg/kg, CVMP, 1997), sheep (16 mg/kg, Corum et al., 2018), and horse (>4 mg/kg, Jaussaud et al., 1992).…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the study, a catheter was placed into the right and left jugular veins of sheep for drug administration and blood collection, respectively. Levofloxacin (4 mg/kg, Goudah and Hasabelnaby, 2010), tolfenamic acid (2 mg/kg, Corum et al, 2018;Yildiz et al, 2019), and flunixin meglumine (2.2 mg/kg, Welsh et al, 1993) were administered to the sheep as a single IV bolus through the venous line placed in the right jugular vein. In the first period, only levofloxacin was administered to the sheep.…”
Section: Experimental Designmentioning
confidence: 99%
“…However, because the EC 50 level of meloxicam varies based on painful and inflammatory condition, its effectiveness in castration should be determined. Increased plasma concentrations of NSAIDs may increase their undesirable effects (Corum, Corum, Er, Yildiz, & Uney, 2018; Yildiz et al., 2019). It is known that a single dose of meloxicam (1 and 2 mg/kg) is well tolerated in sheep (Woodland et al., 2019).…”
Section: Discussionmentioning
confidence: 99%